Potential Values of Urban Geotourism Development in a Small Polish Town (Pruszków, Central Mazovia, Poland) - Górska-Zabielska, Maria; Zabielski, Ryszard (Quaestiones Geographicae, 2017)
The paper presents abiotic resources which are located in a small town in central Poland. They remain unknown to authorities and inhabitants. For the first time they are illustrated in a scientific paper. The objects of local geological heritage point to geodiversity of this district town in the south-western Mazovia. When the geodiversity is interpreted in a simple, an understandable way, it may become attractive for tourists. We show how abiotic resources located within an urban area can be used to support urban geotourism development. The scientific, educational and aesthetic values of these resources may create the town image in accordance with the principles of environmental protection.